The Relation of Work Environment and Stress in Classroom Management among Preschool Teachers - Ambotang, Abdul Said; Mohd Hashim, Muhamad Hisyam (Journal of Techno-Social, 2010)
The purpose of this research is to observe how far preschool teachers endure stress in carrying out their job which is influenced by the work climate including the management of classroom. This research is carried out by choosing a group of 55 preschool teachers as respondents in the district of Keningau Sabah. Data is analyzed using descriptive method (mean), inferential (T-test) Statistic, one way ANOVA and Pearson correlation. Result showed that there were high positive relationships between the work climate with stress level among the teachers. (r = 0.807, p